Stress and Adaptability among English Lecturers: An Interview Analysis - Haryati Haryati; Diyah Iis Andriani (Universitas Hamzanwadi, 2022)
Covid-19 pandemic affects on education and leads to stress as a timeless problem in teaching process in schools or universities. Lectures need to find the joy of their teaching activities and make them comfort at working place by having adaptability acquired from surroundings. The study aims to find out the sources of stress among English lecturers and how they overwhelm the stressful situation. This study applies the descriptive qualitative method to elaborate the analysis. It also engages 6 EFL lecturers of English Department of Universitas Pamulang selected from some categories: working more than six years and showing the high level of stress. They are selected through the questionnaire distribution. Furthermore, the writers conducted an in-depth semi-structured interview to obtain the data. The interview focuses on seeking the two main points: to identify and describe the source of stress in teaching process during the pandemic and to enlighten aspects that assist the lecturers to have adaptability in the stressful circumstance. As the results, the participants share the factors why they get burnout within pandemic circumstances: E-learning system, other system changes, students’ low communication, workload and impromptu task; moreover, they share how to adapt with the situation they face: family relationship, positive personality, positive vibes, and working partners. These assist the lecturers to encourage themselves to work more.